2010
DOI: 10.1111/j.1750-3841.2010.01659.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer and Nutrient Absorption in a Simulated Model of Small Intestine

Abstract: There is an increasing need to understand how food formulations behave in vivo from both food and pharma industries. A number of models have been proposed for the stomach, but few are available for the other parts of the gastrointestinal tract. An experimental rig that simulates the segmentation motion occurring in the small intestine has been developed. The objective of developing such an experimental apparatus was to study mass transport phenomena occurring in the lumen and their potential effect on the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 40 publications
2
81
0
3
Order By: Relevance
“…This showed that the homogenised sample viscosity of FC was drastically changed by addition of SIF, indicating higher starch hydrolysis. The physical texture of food, such as intact grain structure, affects starch digestion and the absorption of its hydrolysis products (Singh et al, 2013;Tharakan, Norton, Fryer, & Bakalis, 2010). Thus, the digestive property of cooked rice would relate to the viscosity of its homogenised materials, which varied by cooking degree.…”
Section: Rice Slurry Particle Size Analysis and Apparent Viscositymentioning
confidence: 99%
“…This showed that the homogenised sample viscosity of FC was drastically changed by addition of SIF, indicating higher starch hydrolysis. The physical texture of food, such as intact grain structure, affects starch digestion and the absorption of its hydrolysis products (Singh et al, 2013;Tharakan, Norton, Fryer, & Bakalis, 2010). Thus, the digestive property of cooked rice would relate to the viscosity of its homogenised materials, which varied by cooking degree.…”
Section: Rice Slurry Particle Size Analysis and Apparent Viscositymentioning
confidence: 99%
“…Similarly, several studies, both in vitro and in vivo, have shown that soluble fibres such as guar gum, (1-3,1-4)-␤-d-glucan and arabinoxylan increase the viscosity of the hydrolysing medium, slowing down hydrolysis of macronutrients by impeding the enzyme-substrate interaction (Dhital, Dolan, Stokes, & Gidley, 2014;Dunaif & Schneeman, 1981;Ellis et al, 2001;Hansen & Schulz, 1982;Leeds, 1979;Montagne, Pluske, & Hampson, 2003;Taylor, 1979;Tharakan, Norton, Fryer, & Bakalis, 2010). Although Dunaif and Schneeman (1981) indicated the potential interaction between fibre source and human pancreatic enzymes, Slaughter, Ellis, Jackson and Butterworth (2002) provided the first evidence for binding of ␣-amylase to guar galactomannan and of inhibition of ␣-amylase activity through a non-competitive mechanism.…”
Section: Introductionmentioning
confidence: 96%
“…In its simplest form the mucus can be considered as a maintained unstirred water layer adjacent to the mucosa across which a concentration gradient develops, in which small molecule nutrients, and indeed many drugs, diffuse across relatively unhindered [15,16]. For larger molecules and nanoscale particulates (of food or pharmaceutical origin) the situation is more complex and mucus can provide both a steric and an interactive barrier substantially reducing the absorption of these components.…”
Section: Barrier Properties Of Small Intestinal Mucusmentioning
confidence: 98%